Brief Report: Typical Visual Updating in Autism. - Weber, Stephanie; Falter-Wagner, Christine; Stöttinger, Elisabeth (Journal of Autism & Developmental Disorders, 2021)
Individuals with Autism Spectrum Disorder (ASD) can struggle with visual updating. In a previous picture morphing study (Burnett and Jellema 2012) adults with ASD recognized the second picture significantly later when seeing one picture gradually changing into another. The aim of the current study was to test whether this previously reported perceptual atypicality may be due to general perceptual deficits. We therefore employed a modified picture morphing task. Against expectations, people with ASD showed typical performance in the task and no general perceptual deficits in relation to the picture morphing paradigm. Our results suggest that reported difficulties with visual updating in ASD may be due to temporal task restrictions and do not reflect a genuine problem with visual updating.